Building-up local management models towards urban sustainability - Karol, Jorge Leonardo (2009)
Sustainable urban development implies a complex management agenda that considers the severe risks associated with the way cities evolve – and the often irreversible nature of their unsustainable growth. This agenda requires specific management models. However, in developing countries, public and community institutions which converge (in subjects, territories, times and policies) in addressing or managing urban evolution are usually characterized by multiplicities and fragmentations, redundancies and emptiness, as well as by contradictory (and even divergent or conflictive) rationalities and speeds. Overlapping of various jurisdictional scales is worsened by their institutional disconnections based on the survival of technical / departmental cleavages and also conceptual and ideological disarticulation between policies – even those ones programmed by a same governmental area. These management scenarios inhibit them to address the complexity of the systemic linkages between physical, functional, economic and social processes that characterize urbanization processes, and preclude States from steering cities’ transition towards increasingly sustainable development patterns, articulating planning, decision- making and operation of institutional goals, policies and actions. These barriers and constraints to integrating the management of sustainability have a quasi-fractal character. Their manifestations can usually be identified at every single point – from macro to micro, from operational to political levels and vice-versa – of the logical sequence that connects all components of management models. Thus, current management patterns at local levels actually enhance and (re)produce differential vulnerabilities and urban un-sustainability. The paper argues that the nature of these types of decisional processes and circuits is essentially political - and not only “technically rational”, as prescriptive institutional design models indicate. Transversal articulations require the systematic and progressive building-up of specific management models and – moreover – promoting continuous inter-institutional learning strategies. It is suggested that these strategies not only may constitute sustainable urban projects but they may also act as their feasibility conditions. Thus, an important task ahead lies in the sphere of local governance, seeking ways to integrate research, assessment and decision-support activities into the design of appropriate management models. It is argued that when focus is placed on the development and progressive implementation of relational models – in fact, boundary organizations – at the local level, this may effectively foster joint learning as well as build-up institutional settings oriented to manage transitions to sustainability. To this end, the paper explores the potentiality of several conceptual frameworks, organizational clues and communication/planning instruments